2023
DOI: 10.3389/fsurg.2023.1131137
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of esketamine for postoperative analgesia in pediatric patients with hypospadias

Abstract: ObjectiveTo explore the safety and efficacy of the combination of continuous intravenous infusion of esketamine with sacral block for postoperative analgesia in pediatric patients undergoing surgery for hypospadiasMethodsPediatric patients (n = 77) undergoing surgery for hypospadias were randomized into two groups: a hydromorphone group (H group, initial dose, 0.02 mg/kg; maintenance dose, 0.01 mg/kg/h) or an esketamine group (E group, initial dose, 0.3 mg/kg; maintenance dose 0.15 mg/kg/h). Caudal epidural bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Furthermore, esketamine has also been reported to significantly reduce the incidence of emergent agitation and inflammation levels after tonsillectomy ( Li et al, 2022 ; Liu et al, 2023 ). Another study involving 77 children undergoing hypospadias surgery demonstrated that, compared with hydromorphone combined with sacral block, esketamine combined with sacral block significantly reduced the incidence of hypotension and respiratory depression as well as shortened the time to first bowel movement ( Xu et al, 2023 ). Additionally, Zhang et al, (2023b) conducted a meta-analysis of 19 clinical trials and pointed out that, compared with the placebo or blank, the esketamine significantly shortened the postoperative recovery time, reduced pain and complication rates, and improved quality of life in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, esketamine has also been reported to significantly reduce the incidence of emergent agitation and inflammation levels after tonsillectomy ( Li et al, 2022 ; Liu et al, 2023 ). Another study involving 77 children undergoing hypospadias surgery demonstrated that, compared with hydromorphone combined with sacral block, esketamine combined with sacral block significantly reduced the incidence of hypotension and respiratory depression as well as shortened the time to first bowel movement ( Xu et al, 2023 ). Additionally, Zhang et al, (2023b) conducted a meta-analysis of 19 clinical trials and pointed out that, compared with the placebo or blank, the esketamine significantly shortened the postoperative recovery time, reduced pain and complication rates, and improved quality of life in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ying Zhang et al found the application of esketamine-dexmedetomidine in an analgesic pump in patients undergoing scoliosis correction significantly reduced the incidence of moderate to severe pain within 72 h and the incidence of moderate-to-severe postoperative pain was reduced by 24% [ 21 ]. Esketamine alone in analgesia pumps has also been shown to provide effective postoperative pain relief [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%